Alternating Hemiplegia and Cardiac Dysrhythmia - J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators at the National Hospital for Neurology and Neurosurgery, Queen Square, London, and multiple centers in the UK, Europe, US, Melbourne, Australia, and Canada, analyzed ECG recordings of 52 patients with alternating hemiplegia from 9 countries; all had whole-exome, whole-genome, or direct Sanger sequencing of ATP1A3; 47 had a confirmed missense mutation in ATP1A3.